ISOLASI DAN KARAKTERISASI BAKTERI INDIGEN PENGURAI LEMAK PADA LIMBAH CAIR BATIK TULUNGAGUNG - Fidiastuti, Hasminar Rachman; Lathifah, Anis Samroatul; Amin, Mohamad; Utomo, Yudhi (Universitas Muhammadiyah Surakarta, 2020)
The native bacteria have a wide life habitat and have an important role as agents in the bioremediation process of waste. Batik as one of the products of Indonesian character, has become a contributor of liquid waste that can reduce water quality. Besides being rich in dyes, batik waste is also rich in fat content. The fat content in batik waste comes from the processing (coating the fabric with a layer of wax) and washing is done repeatedly. Fat has properties that are not soluble in water and is an organic material, which if high concentrations can reduce water quality. This study aims to isolate, identify, and measure the ability of indigenous bacteria to reduce fat content in liquid waste in vitro. The method used is experimental research. Isolation and culture using Busnall Hass media enriched with 1% olive oil, then proceed with a series of biochemical tests for the purpose of characterizing indigenous bacterial isolates. The results showed that Bacillus subtilis and Pseudomonas fluorescens have the potential to reduce the fat content of batik liquid waste.